تحليل الأخطاء اللغوية التطبيقية - Khayun, Khairul Azhar; Yaacob, Solehah@Nik Najah Fadilah (The Scientific Institute For Advanced Training and Studies, 2019)
The purpose of learning languages is to identify a new culture and experiences sharing. It`s encourage students' analytical skills, creativity and problem solving. The study focus on comparative analysis on the similarities and differences between Arabic and Malay language. This study is to discover the principles that perhaps could be applied for problem solving in language teaching or translation, To emphasis on transferring, interference and equivalence by tracking the foreign language problems that could be expected while learning the second language by comparing two or more linguistic families either in highlighting the similarities or differences between them.